The Medicinal Uses of Tinospora Cordifolia (Gurjo) - Adhikari, Suraj Raj; Pokhrel, Kusum (Himalayan Biodiversity, 2019)
Tinospora cordifolia is a perennial, climbing deciduous shrub. This plant belongs to the family Menispermaceae. A variety of phytochemical constituents have been isolated from different parts of T. cordifolia. These compounds belong to different groups such as alkaloids, steroids, diterpenoid lactones, aliphatic compounds, glycosides and polysaccharides. It is a widely used plant in Ayurvedic systems of medicine. Stem, roots and leaves are the most important parts of the plant, which are used in traditional systems of medicines. It possesses anti-neoplastic, antioxidant, anti-hyperglycemic and hepatoprotective properties. It is the important medicinal plant used in traditional Ayurvedic medicine for the treatment of fever, cold, diabetes, respiratory tract infections etc. This paper presents an appraisal of medicinal properties and pharmaceutical importance of Tinospora cordifolia.